EFEK PENGGUNAAN ABU GOSOK DAN SERBUK BATA MERAH PADA PEMBUATAN TELUR ASIN TERHADAP KANDUNGAN MIKROBA DALAM TELUR (THE EFFECT OF USING THE ASH AND THE RED BRICK POWDER IN MAKING OF THE SALTED EGGS TO THE MICROBIAL CONTENT OF THE EGGS) - Heru Yuniati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2011)
ABSTRACT Background: Salting is a way of preserving eggs with the dough / salt solution to boiling and boil for some time. As mixing the dough salt to soak the eggs, rub ash is commonly used in comparison with red brick powder. Purpose: determine the ability of red brick powder media in inhibiting bacteria than rub ash. Material and Method: Ten salted egg is made using a mixture of ash, salt and water in the ratio 4:2:2 ml, While ten more salted egg is made using a mixture of red brick powder, salt, and water in the ratio 4:2:2. Once the dough is well blended, each egg wrapped in dough evenly with a thickness of ± 2 mm. Then the eggs are stored in a plastic bucket in the open space. Microbial testing performed on total bacteria, and yeasts, as well as testing done to contain coliform, E. coli and Salmonella / Shigella on days 0, 5, 10, 15, and 20. Results: The total bacteria and yeasts in the two salted egg products decreased during salting, except on days -20, where an increase in total bacteria on salted egg with rub ash medium, but not on salted eggs with red brick powder medium. At the end of salting, the total number of bacteria of salted eggs for 4 x 102 and 0.9 x 102 colonies / gram, and total yeast and 0.45 x 102 8.7 x 102 colonies / gram. Conclusion: Salted eggs are made ​​using rub ash and red brick powder did not contain coliform bacteria, E. coli and Salmonella / Shigella, while the total number of bacteria and yeasts in the egg there is a difference. Keywords: Egg sauce, rub ash, red brick dust, microbes     ABSTRAK Latar Belakang: Pengasinan adalah cara mengawetkan telur dengan adonan garam dan merebusnya sampai mendidih selama beberapa waktu. Sebagai pencampur dalam adonan garam digunakan abu gosok dibandingkan dengan serbuk bata merah. Tujuan: mengetahui kemampuan media serbuk bata merah dalam menghambat bakteri dibandingkan dengan abu gosok. Bahan dan Cara: Sepuluh butir telur asin dibuat menggunakan campuran abu gosok, garam dapur, dan air dengan perbandingan 4:2:2 ml, sedangkan sepuluh butir telur asin lagi dibuat menggunakan campuran serbuk bata merah, garam dapur, dan air dengan perbandingan 4:2:2. Setelah adonan pengasin tercampur rata, setiap telur dibungkus dengan adonan secara merata dengan ketebalan ±2 mm. Kemudian telur disimpan dalam ember plastik pada ruang terbuka. Pengujian mikroba dilakukan terhadap total bakteri, dan khamir, serta pengujian kandungan  koliform, E. coli dan Salmonella/Shigella pada hari ke- 0, 5, 10, 15, dan 20. Hasil: Total bakteri dan khamir pada ke-2 produk telur asin selama pengasinan terjadi penurunan, kecuali pada penggaraman hari ke-20, di mana terjadi kenaikan total bakteri pada telur asin dengan media abu gosok, tetapi tidak pada telur asin dengan media serbuk bata merah. Di akhir penggaraman, angka total bakteri telur asin sebesar 4 x 102 dan 0,9 x 102 koloni/gram, serta total khamir 0,45 x 102 dan 8,7 x 102 koloni/gram. Kesimpulan: Telur asin yang dibuat dengan menggunakan abu gosok dan serbuk bata merah tidak mengandung bakteri coliform, E. coli dan Salmonella/Shigella, sedangkan jumlah total bakteri dan khamir pada kedua telur ada perbedaan. [Penel Gizi Makan 2011, 34(2): 131-137]   Kata kunci: Telur asin, abu gosok, serbuk bata merah, mikroba.